PERFORMANCE AND DECISION SUPPORT SYSTEM FOR CANE SUGAR PRODUCTION PROCESS CONTROL AT PT. RAJAWALI II, JATITUJUH FACTORY UNIT, MAJALENGKA - Marimin, Andes Ismayana dan Annastia Lohjayanti (Department of Agroindustrial Technology, Bogor Agricultural University, 2009)
Main problem in sugar production is inefficiency of process due to unreliable old machines and equipments. The second problem is low performance of sugar processing, and the third is due to the inefficiency of production management inovation of the company. The objectives of this research were to identify sugar process production factors, process monitoring and capability measurement in each step of process, identification of critical points on sugar processing, production efficiency in PG Jatitujuh, to construct the decision support system for formulating cane sugar production process control. We named the system as SWEETCON.PROSION which is able to provide alternatives for monitoring the production process, and for maintaining scheduling. This system consists of a model base management system, a database management system, and a dialogue management system that are integrated within a central processing system. It is suported with four models, namely critical component model, process performance model, production efficiency model, and process control model. Process performance analysis shows that all of the process stations were under controlled. Critical component analysis shows that extraction machines was the most critical component. Relative efficiency analysis of each indicator shows that all indicators were efficient. However, absolute efficiency analysis showed that the final product environment and input were inefficient both technically and economically. It is shown that technical efficiency of final product environmental was 31.90%, technical efficiency of input was 73%, economical efficiency of final product environmental was 43% and economical efficiency of input was 125.5%. The overall decision hierarchy process control analysis shows that the milling station was the most critical process, and it is to be controlled accordingly. Keywords :equipment critically rating, analytical hierarchy process, data envelopment analysis.